2020
DOI: 10.3389/fpsyg.2020.573793
|View full text |Cite
|
Sign up to set email alerts
|

How Leader-Member Exchange Affects Creative Performance: An Examination From the Perspective of Self-Determination Theory

Abstract: It has been shown that leadership is a major factor that influences creative performance. Although past studies have found that leader-member exchange (LMX) has direct effects on employee creative performance, there continues to be a lack of research examining how the LMX relationship mediates creative performance. This study used self-determination theory to examine the mediating effects of the LMX relationship on creative performance through attitudinal and emotional processes. Participants were supervisors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 64 publications
1
28
0
4
Order By: Relevance
“…The hypotheses were supported. The results for all 4 factors of turnover intention were consistent with past research (Molla, 2020;Laosebikan et al, 2018;Xie et al, 2020;Parveen, 2019) in which it was also found that employees job performance is influenced by job satisfaction, leadership member exchange, emotional intelligence and organizational commitment.…”
Section: Influence Of Job Satisfaction Leadership Member Exchange Emo...supporting
confidence: 90%
“…The hypotheses were supported. The results for all 4 factors of turnover intention were consistent with past research (Molla, 2020;Laosebikan et al, 2018;Xie et al, 2020;Parveen, 2019) in which it was also found that employees job performance is influenced by job satisfaction, leadership member exchange, emotional intelligence and organizational commitment.…”
Section: Influence Of Job Satisfaction Leadership Member Exchange Emo...supporting
confidence: 90%
“…In particular, we join the call for more research that points to mechanisms that explain the association between SDT and organizational outcomes ( LeBreton et al, 2018 ) and we simultaneously test two relational mediators linked to social exchange (i.e., LMX) and social contagion (i.e., collective narcissism) that explain the influence of SDT on ratings of team innovation and performance. Previous research has shown the association between leaders’ behaviors and LMX, as well as the beneficial effects of high quality LMX for positive individual behaviors and outcomes ( Schuh et al, 2018 ; Andersen et al, 2020 ; Götz et al, 2020 ; Xie et al, 2020 ). Similarly, previous research has explored the way social contagion mechanisms explain the association between leadership behavioral tendencies (i.e., leader humility) and emergent states in teams (i.e., collective humility) ( Owens and Hekman, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, recent research indicates it is also important to consider psychological need satisfaction as an antecedent of positive leadership styles, as to better understand why leaders engage into behaviors conductive of such styles ( Paas et al, 2020 ). Second, prior work has mostly adopted a single level approach to psychological need satisfaction, overlooking how psychological need satisfaction is embedded in complex relations between leaders and followers ( Kuvaas and Buch, 2019 ; Xie et al, 2020 ) that cross multiple levels of analysis ( Schreurs et al, 2014 ; Batistič et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we advance that this trickling down takes place through interpersonal exchange processes between leaders and employees, as exemplified by leader-member exchange (LMX). LMX refers to the fact that leaders develop differentiated relationships with their employees ( Graen and Uhl-Bien, 1995 ), where high-quality relationships are characterized by exchanges based on mutual trust, respect, liking, and influence ( Liden and Maslyn, 1998 ) and lead to positive outcomes for both parties ( Graen and Uhl-Bien, 1995 ; Dulebohn et al, 2012 ; Xie et al, 2020 ). Since LMX is considered as need-driven ( Dulebohn et al, 2012 ) and need-satisfying process ( Kuvaas and Buch, 2019 ) that connects multiple levels of analysis ( Liao et al, 2019 ), we propose that LMX constitutes a mechanism through which leader psychological need satisfaction trickles down to employees, from a dyadic viewpoint.…”
Section: Introductionmentioning
confidence: 99%